Verbal discourtesy towards the Venezuelan community in news of events in the newspaper Correo - Castro Yauri, Mabel Alelí (2022)
This article analyzes the use of the words venezolano and extranjero in a sample of news items taken from the website of the Peruvian newspaper Correo. The objective of the research is to demonstrate that these words are used as resources of verbal discourtesy. For this purpose, the context of their use was determined at the macrotextual level (topic, and types of discourse subjects) and microtextual level (types of utterances). According to the analysis, we identified that these voices in some contexts adopt a negative connotation, since through them the Venezuelan collective residing in Peru is associated with delinquency, which affects their group image. Likewise, although these voices are not associated with other types of negative values in other contexts, they do affect their desire for group affiliation.